2017
DOI: 10.1109/tmag.2017.2713837
|View full text |Cite
|
Sign up to set email alerts
|

Batteryless Hall Sensor Operated by Energy Harvesting From a Single Wiegand Pulse

Abstract: We operated a Hall sensor using energy harvested from a magnetic wire. A battery-less sensor is expected to be a key device for the internet of things (IoT). Magnetization reversal in magnetic wires with bistable magnetization states induces a pulse voltage in a pickup coil. The amplitude of the voltage is independent of the applied field frequency, down to zero. This fast magnetization reversal is accompanied by a large Barkhausen jump, which has been known as the Wiegand effect. Electricity generation using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 23 publications
4
36
0
Order By: Relevance
“…In addition to its use as the power source of medical devices, the Wiegand sensor can also be used as an energy-harvesting module and power source for the battery-less operation of electronic devices. [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its use as the power source of medical devices, the Wiegand sensor can also be used as an energy-harvesting module and power source for the battery-less operation of electronic devices. [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Then the internal circuit parameters in the equivalent circuit of the Wiegand sensor, especially the inductance of the receiver coil, should be taken into consideration. Although the application of the Wiegand sensor for the battery-less operation of a rotary encoder [9] is an attractive topic, particularly from the point of view of the industry, only few articles on the Wiegand sensor have been published [10,11] other than those by our group [7,8,12,13]. As Saggini et al reported for the circuit analysis of the Wiegand sensor for low-power energy harvesting solutions [10], it is significant to study the circuit parameters for applications of the Wiegand sensor.…”
Section: Introductionmentioning
confidence: 99%
“…5), in which both of measured full and minor loops have been shown. The magnetization alignment of the soft layer and the hard core can be either in a parallel state or an antiparallel state, as shown in Fig.…”
Section: A D V a N C E P U B L I C A T I O Nmentioning
confidence: 85%
“…the FeCoV wire of 0.25 mm diameter 4,5) . The volumes of the soft and hard core were 23% and 77%, respectively.…”
Section: A D V a N C E P U B L I C A T I O Nmentioning
confidence: 99%
See 1 more Smart Citation